2011
DOI: 10.1007/s11130-011-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Nutritional Value of Unripe Banana Flour (Musa acuminata, var. Nanicão)

Abstract: Banana flour obtained from unripe banana (Musa acuminata, var. Nanicão) under specific drying conditions was evaluated regarding its chemical composition and nutritional value. Results are expressed in dry weight (dw). The unripe banana flour (UBF) presented a high amount of total dietary fiber (DF) (56.24 g/100 g), which consisted of resistant starch (RS) (48.99 g/100 g), fructans (0.05 g/100 g) and DF without RS or fructans (7.2 g/100 g). The contents of available starch (AS) (27.78 g/100 g) and soluble suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 29 publications
5
68
3
7
Order By: Relevance
“…The GBP produced in the present study was elaborated from the variety Balbisiana (prata) and presented lower total phenolic compound contents than those observed by Menezes et al (2011). This difference might be attributed to the varieties of banana used in both studies and also to the phenolic extraction method used by the authors, where the sample was subjected to extraction by an ultrasound-assisted method.…”
Section: Total Phenolic Compoundsmentioning
confidence: 51%
See 1 more Smart Citation
“…The GBP produced in the present study was elaborated from the variety Balbisiana (prata) and presented lower total phenolic compound contents than those observed by Menezes et al (2011). This difference might be attributed to the varieties of banana used in both studies and also to the phenolic extraction method used by the authors, where the sample was subjected to extraction by an ultrasound-assisted method.…”
Section: Total Phenolic Compoundsmentioning
confidence: 51%
“…However, the total phenolic compounds of the wheat flour could not be determined, probably because the amount present was below the quantification threshold of the method used. Menezes et al (2011) investigated the total phenolic compound content of the GBP from the banana variety Cavendish, known as nanicão in Brazil, and observed a content of 50.65 ± 0.08 mg GAE/100 g dry matter.…”
Section: Total Phenolic Compoundsmentioning
confidence: 99%
“…§ § Response of isolated pancreatic islets to glucose 16.7 mM in relation to the secretion response to glucose 5.6 mM (reference 100 %), n=3 rats/group combined with the RS physiological properties, enable these ingredients to be used for development of new products with functional properties [12,31]. Analyses of the unripe banana flour showed that this ingredient is rich in dietary fiber and resistant starch, has low energy and available carbohydrates, as well as moderate antioxidant activity [32]. The initial stage of maturation and the process which the unripe banana goes through are extremely important once they may determine its final RS content.…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%
“…However, others nutrients like calcium, magnesium, potassium, sodium that also are necessary for life, but are present in higher quantities. Research carried from plant sources of conventional and unconventional demonstrate the existence of significant levels of these nutrients, contemplating the needs of recommended daily intakes [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%